Strengthening and toughening regulation and control method for multi-stage sequential TiAl single crystal

Through hot press regulation, isothermal heat treatment and the combination of the two, the γ phase and α2 phase are refined, which solves the problem of low strong plasticity of TiAl single crystal, and achieves a significant improvement in the full-sheet refinement and toughening performance of multi-stage sequence TiAl single crystal, meeting the high mechanical performance needs of aerospace engine materials.

CN119530985AActive Publication Date: 2025-02-28YANSHAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411714647.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

TiAl single crystal has low strong plasticity and cannot meet the high mechanical performance requirements of aero engine materials.

Method used

Three toughening and toughening control methods are adopted: hot press regulation, isothermal heat treatment and the combination of the two. By refining the γ phase and the α2 phase, the full-sheet layer refinement of the multi-stage sequence TiAl single crystal is achieved.

Benefits of technology

The strength and toughening performance of the multi-stage sequence TiAl single crystal has been significantly improved, so that its tensile strength reaches 653~1006MPa at room temperature at a tensile rate of 10-4s-1 and its elongation is 13.6~24.5%, meeting the higher mechanical performance requirements of aerospace engine materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530985A_ABST
    Figure CN119530985A_ABST
Patent Text Reader

Abstract

The invention discloses a strengthening and toughening regulation and control method for a multi-stage sequential TiAl single crystal, and belongs to the technical field of strengthening and toughening of metal materials. According to the strengthening and toughening hot-pressing regulation and control method for the multi-stage sequential TiAl single crystal, the multi-stage sequential TiAl single crystal with the refined gamma phase is obtained by controlling the temperature, the pressure, the heat preservation time and the like. According to the strengthening and toughening isothermal heat treatment regulation and control method for the multi-stage sequential TiAl single crystal, the multi-stage sequential TiAl single crystal with the refined alpha2 phase is obtained by controlling the vacuum degree, the temperature, the heat preservation time and the like. The invention provides a regulation and control method combining hot pressing and isothermal heat treatment to obtain the full-lamella refined multi-stage sequential TiAl single crystal. According to the multistage sequential TiAl single crystal regulated and controlled through the method, the mechanical property is greatly improved, the yield strength ranges from 653 MPa to 1006 MPa, and the elongation ranges from 13.6% to 24.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of strengthening and toughening of metal materials, and particularly relates to a method for regulating and controlling the strengthening and toughening of a multi-level sequenced TiAl single crystal. Background Art

[0002] In recent years, the field of aerospace technology has developed rapidly, actively promoting the development of my country's aerospace high-tech materials, which is related to national defense security, economic transformation and future strategic layout. In view of the excellent high-temperature mechanical properties of nickel-based superalloys, nickel-based superalloy materials are currently mostly used in aerospace engines. Although nickel-based superalloys have good high-temperature properties, their high density (8.2-8.9 g / cm 3 ) will greatly increase the weight of the engine, and this problem has become a constraint on its vigorous development.

[0003] The multi-level TiAl single crystal is a full-lamellar structure with parallel phase interfaces and twin interfaces. It has a high initial melting temperature (1585℃) and a density (3.9g / cm 3 ) is less than half of the nickel-based high-temperature alloy, and is a promising aero-engine material. Today, TiAl-4822 alloy has been used by GE in the low-pressure turbines of 747 and 787 aircraft, and this application has also achieved huge economic benefits. Since aero-engines have very high requirements for the mechanical properties of materials, the strength and plasticity of TiAl alloys are still somewhat different from those of nickel-based high-temperature alloys.

[0004] Therefore, TiAl single crystals cannot be widely used in engines at present. In order to further expand the application scope of TiAl single crystals, it is necessary to strengthen and toughen them to meet more application needs. Summary of the invention

[0005] In view of the defects existing in the above-mentioned prior art, in order to solve the technical problem that the strength and plasticity of TiAl single crystals are low and cannot meet the requirements of the materials prepared in aerospace engines, the purpose of the present invention is to design and provide three multi-level sequence TiAl single crystal strengthening and toughening control process methods, through hot pressing control, isothermal heat treatment and the effective combination of the three methods can achieve the strengthening and toughening of TiAl single crystal materials. The best effect is the third method combining hot pressing control with isothermal heat treatment, which can make the multi-level sequence TiAl single crystal achieve full-layer refinement and meet the requirements of aerospace engine materials for higher mechanical properties.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] In one aspect, the present invention provides a method for hot pressing and regulating the strengthening and toughening of a multi-level TiAl single crystal, comprising the following steps:

[0008] Weigh a multi-level TiAl single crystal sample, cut it into blocks, place it in a hot press, increase the temperature to 1050-1200°C at a heating rate of 10-20°C / min, gradually increase the pressure to 40-85MPa within 5-60min, keep it warm for 5-20h, cool it to room temperature with the furnace, and take out the multi-level TiAl single crystal with refined γ phase.

[0009] In the method for regulating and strengthening the hot pressing of a multi-level sequence TiAl single crystal, the block-shaped multi-level sequence TiAl single crystal is placed in a mold, and when the pressure is increased, the compression direction of the pressure is 90° to the lamellae of the multi-level sequence TiAl single crystal.

[0010] In a second aspect, the present invention provides a γ-phase refined multi-level structured TiAl single crystal prepared by the method.

[0011] In a third aspect, the present invention provides a method for strengthening and toughening a multi-level TiAl single crystal by isothermal heat treatment, comprising the following steps:

[0012] Weigh the multi-level TiAl single crystal sample, cut it into blocks, place it in a high vacuum heat treatment furnace, and evacuate it to 10 - 4 Pa, raise the temperature to 1250-1330°C at a heating rate of 10-20°C / min, keep it warm for 5-24h, cool it to room temperature with the furnace, and take out the TiAl single crystal with refined α2 phase and multi-level structure.

[0013] The strengthening and toughening isothermal heat treatment control method of the multi-level structure TiAl single crystal has a cooling rate of 10 to 20°C / s.

[0014] In a fourth aspect, the present invention provides an α2 phase refined multi-level structured TiAl single crystal prepared by the method.

[0015] In a fifth aspect, the present invention provides a method for regulating a multi-level ordered TiAl single crystal, comprising the following steps:

[0016] (1) Weigh a multi-level TiAl single crystal sample, cut it into blocks, place it in a hot press, increase the temperature to 1050-1200°C at a heating rate of 10-20°C / min, gradually increase the pressure to 40-85MPa within 5-60min, keep it at this temperature for 5-20h, cool it to room temperature with the furnace, and take out a multi-level TiAl single crystal with refined γ phase;

[0017] (2) The multi-level TiAl single crystal with refined γ phase is placed in a high vacuum heat treatment furnace and evacuated to 10 -4Pa, raise the temperature to 1250-1330°C at a heating rate of 10-20°C / min, keep it warm for 5-24h, cool it to room temperature with the furnace, and take out the TiAl single crystal with fully layered refinement and multi-level structure.

[0018] In the control method, the block-shaped multi-level TiAl single crystal is placed in a mold in step (1), and when the pressure is increased, the compression direction of the pressure is 90° to the lamellae of the multi-level TiAl single crystal;

[0019] The cooling rate in step (2) is 10-20°C / s.

[0020] In a sixth aspect, the present invention provides a fully lamellar refined multi-level structured TiAl single crystal prepared by the control method.

[0021] In a seventh aspect, the present invention provides the use of the γ-phase refined multi-level sequenced TiAl single crystal, the α2-phase refined multi-level sequenced TiAl single crystal or the full-lamellar refined multi-level sequenced TiAl single crystal as aerospace materials with strong plasticity.

[0022] In the first slow hot pressing control method of the present invention, under the action of temperature and pressure, the twin interface (γ / γ T ) The 1 / 6<11-2> Shockley partial dislocations on both sides of the {111} plane slide through the crystal in opposite directions, which also leads to the transformation of FCC into HCP structure at the twin interface. This structural transformation is called stress-induced phase transition. After the phase transition, the average width of the lamellae of the multi-level TiAl single crystal will decrease, which is also the reason for its improved strength.

[0023] In the second isothermal heat treatment control method of the present invention, after the temperature is raised to the isothermal phase transition range of the TiAl single crystal, the α2 phase in the TiAl single crystal is transformed into a disordered α phase, and then in the process of cooling, by controlling the cooling rate, the α phase will decompose into the α2 phase and the secondary γ phase. Through isothermal phase transition control, the final multi-level structure TiAl single crystal contains a primary γ phase, an α2 phase, and a secondary γ phase, which successfully refines the lamellae and improves their strength.

[0024] In the third method of combining slow hot pressing regulation and isothermal heat treatment regulation of the present invention, the γ phase is first refined, and then the α2 phase is refined. Finally, through the combined regulation of the two, a fully layered refined multi-level sequence TiAl single crystal is successfully obtained.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention provides a method for strengthening and toughening a multi-level sequenced TiAl single crystal. The multi-level sequenced TiAl single crystal obtained by slow hot pressing is 10-4 s -1 At the tensile rate, the tensile strength is 653-701 MPa and the elongation is 11.7-23.5%. The multi-level TiAl single crystal obtained after the second isothermal heat treatment is 10 -4 s -1 At the tensile rate, the tensile strength is 653-883 MPa, and the elongation is 7.4-22.9%. The third type of TiAl single crystal with a fully layered and refined multi-level structure obtained by combining hot pressing and isothermal heat treatment is 10 -4 s -1 At the tensile rate, the tensile strength is 653-1006 MPa; the elongation is 13.6-24.5%, indicating that the three multi-level sequence TiAl single crystal strengthening and toughening control methods of the present invention are all effective. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Figure 1 is a microstructure diagram of the TiAl single crystal before and after hot pressing at 1200°C and 55MPa for 5h in Example 1, wherein (a) is a micromorphology diagram of the TiAl single crystal before hot pressing; (b) is a micromorphology diagram of the TiAl single crystal after hot pressing; (c) is a statistical diagram of the average width of the γ phase layer of the TiAl single crystal before hot pressing; (d) is a statistical diagram of the average width of the γ phase layer of the TiAl single crystal after hot pressing;

[0028] Figure 2 The room temperature tensile curves of TiAl single crystals regulated by different toughening processes in Examples 1, 4, and 7;

[0029] Figure 3 The microstructure diagrams of the TiAl single crystal before and after hot pressing at 1000°C and 55MPa for 5h in Comparative Example 1, wherein (a) is a micromorphology diagram of the TiAl single crystal before hot pressing; (b) is a micromorphology diagram of the TiAl single crystal after hot pressing; (c) is a statistical diagram of the average width of the γ phase layer of the TiAl single crystal before hot pressing; (d) is a statistical diagram of the average width of the γ phase layer of the TiAl single crystal after hot pressing;

[0030] Figure 4 The microstructure diagram of the sample before and after the isothermal heat treatment at 1310°C for 5h in Example 4, wherein (a) is the morphology diagram of the sample before the isothermal heat treatment; (b) is the morphology diagram of the sample after the isothermal heat treatment; (c) is the statistical diagram of the average width of the α2 phase layer of the sample before the isothermal heat treatment; (d) is the statistical diagram of the average width of the α2 phase layer of the sample before and after the isothermal heat treatment at 1310°C for 5h;

[0031] Figure 5These are the morphology pictures of the TiAl single crystal before and after isothermal heat treatment at 1200℃ and 55MPa for 5h and 1310℃ for 5h in Example 7, where (a) is the morphology picture of the sample before regulation; (b) is the morphology picture of the full-lamellar refinement sample after regulation; (c) is a statistical chart of the average width of the γ phase lamella before regulation; (d) is a statistical chart of the average width of the γ phase lamella of the full-lamellar refinement sample after regulation. DETAILED DESCRIPTION

[0032] The disclosure below provides many different embodiments or examples to implement different structures of the present invention. In order to simplify the disclosure of the present invention, the method steps of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention.

[0033] Embodiment 1:

[0034] A multi-level TiAl single crystal sample (average width of the γ phase layer is 1.42 μm) was prepared into a block sample using an electric spark wire cutting machine and placed in a hot press. The temperature was then raised to 1200°C at a heating rate of 10°C / min, and the pressure was gradually raised to 55 MPa within 30 minutes. The sample was kept at 1200°C for 5 hours. After the heat preservation stage, the sample was cooled to room temperature with the furnace, and then the power was cut off and the TiAl single crystal sample was taken out of the hot press. The structure of the TiAl single crystal sample after the adjustment still maintained a two-phase layer structure, such as Figure 1 Figure 2 is the microstructure diagram of TiAl single crystal before and after hot pressing regulation. It can be seen that the average width of the γ phase of the TiAl single crystal sample after regulation is 611.8nm. Compared with the average width of the γ phase layer of the parent material of 1.42μm, the average width of the γ phase of the TiAl single crystal sample after regulation is significantly reduced.

[0035] The tensile strength and elongation of the TiAl single crystal sample structure after the above adjustment were tested, specifically:

[0036] The present invention uses the EHF-010-OA fatigue machine produced by Shimadzu Corporation of Japan to perform room temperature tensile testing of TiAl single crystals. The tensile specimen is processed into a bone rod shape by diamond wire cutting, the tensile direction is 0° orientation, the specific size of the specimen is 5mm*8mm, and the gauge area size is 1mm*2mm. In order to remove the surface stress of the sample, the tensile specimen needs to be ground with 400#~3000# sandpaper, and then the specimen is mechanically polished, and finally electrolytic polishing is used for treatment. The sample is then mounted on the fixture of the fatigue machine for room temperature stretching. In the above mechanical test, in order to obtain accurate tensile data, samples with different parameters are stretched at least three times and the average value of the three data is selected as a representative.

[0037] The results are as follows Figure 2 As shown in the figure, the structure of the TiAl single crystal sample regulated by the method of Example 1 is 10-4 s -1 At the tensile rate, the tensile strength is 653-701 MPa, and the elongation is 11.7-23.5%.

[0038] Embodiment 2:

[0039] A multi-level TiAl single crystal sample (average width of γ phase lamella 1.42μm) was prepared into a block sample using an electric spark wire cutting machine and placed in a hot press. The temperature was then raised to 1200℃ at a heating rate of 15℃ / min, and then the pressure was gradually raised to 40MPa within 5min. The sample was kept at 1200℃ for 10h. After the insulation stage, it was cooled to room temperature with the furnace, and then the power was cut off and the TiAl single crystal sample was taken out of the hot press. The structure of the TiAl single crystal sample after the adjustment still maintained a two-phase lamella structure. The average width of the γ phase was 620.4nm, and the γ phase width was successfully and effectively adjusted.

[0040] Embodiment 3:

[0041] The multi-level TiAl single crystal sample (average width of γ phase layer 1.42μm) was prepared into a block sample using an electric spark wire cutting machine and placed in a hot press. Then the temperature began to rise to 1050℃, with a heating rate of 20℃ / min, and then the pressure was gradually increased to 85MPa within 60min, and kept at 1050℃ for 20h. After the insulation stage, it was cooled to room temperature with the furnace, and then the power was cut off and the TiAl single crystal sample was taken out of the hot press. Finally, the structure of the TiAl single crystal sample after regulation still maintained a two-phase layer structure. The average width of its γ phase was 616.3nm, and the γ phase width was successfully effectively regulated.

[0042] Comparative Example 1:

[0043] The multi-level TiAl single crystal sample (average width of the γ phase layer is 1.42μm) was prepared into a block sample using an electric spark wire cutting machine and placed in a hot press. Then the temperature was raised to 1000℃ at a heating rate of 10℃ / min, and then the pressure was raised to 55MPa. It was kept at 1000℃ for 5h. After the insulation stage, it was cooled to room temperature with the furnace, and then the power was cut off and the TiAl single crystal sample was taken out from the hot press. The structure of the TiAl single crystal sample after the adjustment still maintained a two-phase layer structure, such as Figure 3 The figure shows the microstructure of the TiAl single crystal before and after hot pressing regulation, where the average width of the γ phase is 1.35 μm, which is not much different from the average width of the γ phase layer of the parent material TiAl single crystal sample. This may be due to the fact that the temperature is too low and the γ phase width cannot be effectively regulated.

[0044] Embodiment 4:

[0045] The multi-level TiAl single crystal sample (average width of α2 phase layer is 116.82nm) was prepared into a block sample using a wire-cut electric discharge machine, and then placed in a high vacuum heat treatment furnace, and the vacuum degree was pumped to 10 -4 Pa. Then the temperature was raised to 1310℃, the heating rate was 10℃ / min, and the temperature was kept at 1310℃ for 5h. After the heat preservation stage, the sample was cooled to room temperature with the furnace, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. The structure of the TiAl single crystal sample after the adjustment still maintained a two-phase layer structure, such as Figure 4 The figure shows the microstructure of TiAl single crystal before and after isothermal heat treatment. The average width of the α2 phase is 70.59 nm, which is 39.57% lower than that of the base material, and the α2 phase width is effectively refined.

[0046] The tensile strength and elongation of the TiAl single crystal sample structure after the above adjustment were tested, and the specific test method was the same as that in Example 1. The results are as follows Figure 2 As shown in the figure, the multi-level TiAl single crystal after isothermal heat treatment is 10 -4 s -1 At the tensile rate, the tensile strength is 653-883 MPa, and the elongation is 7.4-22.9%.

[0047] Embodiment 5:

[0048] The multi-level TiAl single crystal sample (average width of α2 phase layer is 116.82nm) was prepared into a block sample using a wire-cut electric discharge machine, and then placed in a high vacuum heat treatment furnace, and the vacuum degree was pumped to 10 -4 Pa or less. Then the temperature was raised to 1250℃, the heating rate was 15℃ / min, and the temperature was kept at 1250℃ for 24h. After the heat preservation stage, the furnace was cooled to room temperature, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. Finally, the structure of the TiAl single crystal sample after regulation still maintained a two-phase layer structure, in which the average width of the α2 phase was 72.31nm, and the α2 phase width was effectively refined.

[0049] Embodiment 6:

[0050] The multi-level TiAl single crystal sample (average width of α2 phase layer is 116.82nm) was prepared into a block sample using a wire-cut electric discharge machine, and then placed in a high vacuum heat treatment furnace, and the vacuum degree was pumped to 10 -4Pa or less. Then the temperature was raised to 1330℃, the heating rate was 20℃ / min, and the temperature was kept at 1330℃ for 15h. After the heat preservation stage, the furnace was cooled to room temperature, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. Finally, the structure of the TiAl single crystal sample after regulation still maintained a two-phase layer structure, in which the average width of the α2 phase was 70.12nm, and the α2 phase width was effectively refined.

[0051] Comparative Example 2:

[0052] The multi-level TiAl single crystal sample (average width of α2 phase layer is 116.82nm) was prepared into a block sample using a wire-cut electric discharge machine, and then placed in a high vacuum heat treatment furnace, and the vacuum degree was pumped to 10 -4 Pa or less. Then the temperature was raised to 1200℃, the heating rate was 10℃ / min, and the temperature was kept at 1200℃ for 5h. After the heat preservation stage, the furnace was cooled to room temperature, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. The structure of the TiAl single crystal sample after the control still maintained a two-phase layer structure. Due to the low temperature, the width of the α2 phase could not be effectively controlled.

[0053] Embodiment 7:

[0054] The multi-level TiAl single crystal sample was prepared into a block sample using an electric spark wire cutting machine, and then placed in a hot press. The temperature was then raised to 1200°C at a heating rate of 10°C / min, and then the pressure was gradually raised to 55MPa within 30min. The sample was kept at 1200°C for 5h. After the heat preservation stage, the sample was cooled to room temperature with the furnace, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. Subsequently, the sample was placed in a high vacuum heat treatment furnace and the vacuum was pumped to 10 by a mechanical pump and a molecular pump. - 4 Pa. Then the temperature was raised to 1310℃, the heating rate was 10℃ / min, and the temperature was kept at 1310℃ for 5h. After the heat preservation stage, the sample was cooled to room temperature with the furnace, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. The structure of the TiAl single crystal sample after the adjustment still maintained a two-phase layer structure, such as Figure 5 The morphology of the TiAl single crystal before and after regulation and the statistical diagram of the γ phase lamella width are controlled by combining hot pressing and isothermal heat treatment. It can be seen that the average width of the γ phase lamella is refined from 1.42μm in the growth state to 65.53nm, and the widths of the two phase lamellae are uniform, successfully achieving full lamella refinement.

[0055] The tensile strength and elongation of the TiAl single crystal sample structure after the above adjustment were tested, and the specific test method was the same as that in Example 1. The results are as follows Figure 2As shown in the figure, the TiAl single crystal with full-lamellar refinement obtained after regulation is 10 -4 s -1 At the tensile rate, the tensile strength is 653-1006 MPa; the elongation is 13.6-24.5%.

[0056] Embodiment 8:

[0057] The multi-level TiAl single crystal sample was prepared into a block sample using an electric spark wire cutting machine, and then placed in a hot press. The temperature was then raised to 1200°C at a heating rate of 15°C / min, and then the pressure was gradually raised to 40MPa within 5 minutes. The sample was kept at 1200°C for 10 hours. After the heat preservation stage, the sample was cooled to room temperature with the furnace, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. Subsequently, the sample was placed in a high vacuum heat treatment furnace and the vacuum was pumped to 10 by a mechanical pump and a molecular pump. - 4 Pa or less. Then the temperature was raised to 1250℃, the heating rate was 15℃ / min, and the temperature was kept at 1250℃ for 24h. After the heat preservation stage, the furnace was cooled to room temperature, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. Finally, the structure of the TiAl single crystal sample after regulation still maintained a two-phase lamellar structure, and the average width of the γ phase was 68.53nm, and full lamellar refinement was successfully achieved.

[0058] Embodiment 9:

[0059] The multi-level TiAl single crystal sample was prepared into a block sample using an electric spark wire cutting machine, and then placed in a hot press. The temperature was then raised to 1050°C at a rate of 20°C / min, and the pressure was gradually raised to 85MPa within 60min. The sample was kept at 1050°C for 20h. After the heat preservation stage, the sample was cooled to room temperature with the furnace, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. Subsequently, the sample was placed in a high vacuum heat treatment furnace and the vacuum was pumped to 10 by a mechanical pump and a molecular pump. - 4 Pa or less. Then the temperature was raised to 1330℃, the heating rate was 20℃ / min, and the temperature was kept at 1330℃ for 15h. After the heat preservation stage, the furnace was cooled to room temperature, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. Finally, the structure of the TiAl single crystal sample after regulation still maintained a two-phase lamellar structure, and the average width of the γ phase was 67.37nm, and full lamellar refinement was successfully achieved.

[0060] Comparative Example 3:

[0061] The multi-level TiAl single crystal sample was prepared into a block sample using an electric spark wire cutting machine, and then placed in a hot press. The temperature was then raised to 1150°C at a heating rate of 10°C / min, and the pressure was then raised to 55MPa. The sample was kept at 1150°C for 5 hours. After the heat preservation stage, the sample was cooled to room temperature with the furnace, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. Subsequently, the sample was placed in a high vacuum heat treatment furnace and the vacuum was pumped to 10 by a mechanical pump and a molecular pump. -4 Pa or less. Then the temperature was raised to 1350℃, the heating rate was 10℃ / min, and the temperature was kept at 1350℃ for 5h. After the heat preservation stage, the furnace was cooled to room temperature, and then the power was cut off and the TiAl single crystal sample was taken out of the heat treatment furnace. Finally, the structure of the TiAl single crystal sample after regulation was recrystallized, and the whole layer refinement was not successfully regulated.

[0062] Those skilled in the art will readily appreciate other embodiments of the invention after considering the specification and practicing the invention herein. The invention is intended to cover any variations, uses or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art of the invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the invention are indicated by the claims.

[0063] It should be understood that the present invention is not limited to the exact construction that has been described above and shown in the drawings and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

Claims

1. A method for hot pressing and controlling the strengthening and toughening of a multi-level TiAl single crystal, characterized in that: The following steps are involved: Weigh a multi-level TiAl single crystal sample, cut it into blocks, place it in a hot press, increase the temperature to 1050-1200°C at a heating rate of 10-20°C / min, gradually increase the pressure to 40-85MPa within 5-60min, keep it warm for 5-20h, cool it to room temperature with the furnace, and take out the multi-level TiAl single crystal with refined γ phase.

2. The method for hot pressing and toughening a multi-level TiAl single crystal according to claim 1, characterized in that: The block-shaped multi-level sequence TiAl single crystal is placed in a mold, and when the pressure is increased, the compression direction of the pressure is 90 degrees to the lamellae of the multi-level sequence TiAl single crystal.

3. A γ-phase refined multi-level structured TiAl single crystal prepared by the method according to claim 1 or 2.

4. A method for strengthening and toughening a multi-level TiAl single crystal by isothermal heat treatment, characterized in that: The following steps are involved: Weigh the multi-level TiAl single crystal sample, cut it into blocks, place it in a high vacuum heat treatment furnace, and evacuate it to 10 -4 Pa, raise the temperature to 1250-1330°C at a heating rate of 10-20°C / min, keep it warm for 5-24h, cool it to room temperature with the furnace, and take out the TiAl single crystal with refined α2 phase and multi-level structure.

5. The isothermal heat treatment control method for strengthening and toughening a multi-level structured TiAl single crystal according to claim 4, characterized in that: The cooling rate is 10-20°C / s.

6. A TiAl single crystal with refined α2 phase and multi-level structure prepared by the method according to claim 4 or 5.

7. A method for regulating a multi-level structure TiAl single crystal, characterized in that: The following steps are involved: (1) Weigh a multi-level TiAl single crystal sample, cut it into blocks, place it in a hot press, increase the temperature to 1050-1200°C at a heating rate of 10-20°C / min, gradually increase the pressure to 40-85MPa within 5-60min, keep it at this temperature for 5-20h, cool it to room temperature with the furnace, and take out a multi-level TiAl single crystal with refined γ phase; (2) The multi-level TiAl single crystal with refined γ phase is placed in a high vacuum heat treatment furnace and evacuated to 10 -4 Pa, raise the temperature to 1250-1330°C at a heating rate of 10-20°C / min, keep it warm for 5-24h, cool it to room temperature with the furnace, and take out the TiAl single crystal with fully layered refinement and multi-level structure.

8. The control method according to claim 7, characterized in that: The block-shaped multi-level TiAl single crystal in step (1) is placed in a mold, and when the pressure is increased, the compression direction of the pressure is 90° to the lamellae of the multi-level TiAl single crystal; The cooling rate in step (2) is 10-20°C / s.

9. A TiAl single crystal with fully lamellar refinement and multi-level structure prepared by the control method according to claim 7 or 8.

10. Use of the γ-phase refined multi-level structured TiAl single crystal according to claim 1, the α2-phase refined multi-level structured TiAl single crystal according to claim 6, or the full-lamellar refined multi-level structured TiAl single crystal according to claim 9 as aerospace materials with strong plasticity.

Citation Information

Patent Citations

  • TiAl single crystal with controllable phase proportion and regulation and control method thereof

    CN116121876A

  • Electron beam additive manufacturing method of fine-grain fully lamellar structure TiAl alloy

    CN117548687A

  • Heat treatment method for ultrahigh-toughness gamma-TiAl intermetallic compound binary structure

    CN118957463A

  • Tial intermetallic compound single crystal material and preparation method therefor

    US20170268127A1